Variation in acute and community service provision of care of the elderly services across Scotland: fi ndings from the Scottish Care of Older People (SCoOP) initial scoping survey. (2019) - Donaldson, Alison IC; Neal, Samuel R; McAlpine, Christine H; Quinn, Terence; Shenkin, Susan D; Ellis, Graham; Myint, Phyo Kyaw
No abstract available